Effects of persistent modulation of intestinal microbiota on SIV/HIV vaccination in rhesus macaques - Nichole R. Klatt; Courtney Broedlow; Jessica M. Osborn; Andrew T. Gustin; Sandra Dross; Megan A. O’Connor; Ernesto Coronado; Philip Barnette; Tiffany Hensley-McBain; Alexander S. Zevin; Roshell Muir; Alexander Roederer; et al. (npj Vaccines, 2021)
Abstract An effective vaccine to prevent HIV transmission has not yet been achieved. Modulation of the microbiome via probiotic therapy has been suggested to result in enhanced mucosal immunity. Here, we evaluated whether probiotic therapy could improve the immunogenicity and protective efficacy of SIV/HIV vaccination. Rhesus macaques were co-immunized with an SIV/HIV DNA vaccine via particle-mediated epidermal delivery and an HIV protein vaccine administered intramuscularly with Adjuplex™ adjuvant, while receiving daily oral Visbiome® probiotics. Probiotic therapy alone led to reduced frequencies of colonic CCR5+ and CCR6+ CD4+ T cells. Probiotics with SIV/HIV vaccination led to similar reductions in colonic CCR5+ CD4+ T cell frequencies. SIV/HIV-specific T cell and antibody responses were readily detected in the periphery of vaccinated animals but were not enhanced with probiotic treatment. Combination probiotics and vaccination did not impact rectal SIV/HIV target populations or reduce the rate of heterologous SHIV acquisition during the intrarectal challenge. Finally, post-infection viral kinetics were similar between all groups. Thus, although probiotics were well-tolerated when administered with SIV/HIV vaccination, vaccine-specific responses were not significantly enhanced. Additional work will be necessary to develop more effective strategies of microbiome modulation in order to enhance mucosal vaccine immunogenicity and improve protective immune responses.